2020
DOI: 10.1177/0963721420920383
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Working Memory, Long-Term Knowledge, and Statistical Learning

Abstract: Evidence supporting the idea that serial-order verbal working memory is underpinned by long-term knowledge has accumulated over more than half a century. Recent studies using natural-language statistics, artificial statistical-learning techniques, and the Hebb repetition paradigm have revealed multiple types of long-term knowledge underlying serial-order verbal working memory performance. These include (a) element-to-element association knowledge, which slowly accumulates through extensive exposure to an exemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…By contrast, unified representations of entire array configurations are unique, and these traces gain strength for repeated arrays, outcompeting traces of the unique arrays. This conclusion converges with insights from studies implying that individual item-position associations are not sufficient to explain the Hebb effect (Cumming et al, 2003; Fastame et al, 2005; Saito et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…By contrast, unified representations of entire array configurations are unique, and these traces gain strength for repeated arrays, outcompeting traces of the unique arrays. This conclusion converges with insights from studies implying that individual item-position associations are not sufficient to explain the Hebb effect (Cumming et al, 2003; Fastame et al, 2005; Saito et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…This means, in the words of Shimi and Logie (2019), being aware of the contents input to a domain-specific cache, thereby making the episodic long-term memory accessible. We found that performance based on location–item frequency statistics and whole list (array) statistics were similar across the visuospatial and verbal item domain (see also Majerus et al, 2004, Majerus & Oberauer, 2020; Saito et al, 2020). Musfeld et al (2022) observed that learning in the visuospatial domain was slower than in the verbal domain.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, location-item association learning could be accumulated throughout the experiment. The arrangement of this learning schedule was based on the prediction that position-item association learning would be slower than whole-list learning (see Saito et al, 2020, for discussions on this issue). Note that their Hebb lists were always constructed with high-frequency position items.…”
Section: Experiments 1: Simultaneous Presentation With Whole-probe Re...mentioning
confidence: 99%
“…An important property of verbal working memory is that the quality of phonological 1 representations in working memory depends on long‐term knowledge of the statistical distribution of phonological information in the linguistic environment (e.g., Gupta & Tisdale, 2009a; 2009b; Hartley & Houghton, 1996; for a collection of articles from this field, see Thorn & Page, 2008; for a review, see Saito, Nakayama, & Tanida, 2020). The effect of phonotactic frequency is an example of a phenomenon that reflects long‐term serial order knowledge in the phonemic domain.…”
Section: Introductionmentioning
confidence: 99%